Inverse problem for interior spectral data of the hydrogen atom equation - Panakhov, E. S.; Sat, M. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We consider the inverse problem for second-order differential operators with regular singularity and show that the potential function can be uniquely determined by the set of values of eigenfunctions at some interior point and parts of two spectra.